Constraints Faced By Dairy Farmers Of Kheda District Of Middle Gujarat In Adoption Of Improved Animal Husbandry Practises - Raval , Rupesh J.; Chandawat , M.S. (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
Present study was taken up with the specific objectives to identify constraints faced by the dairy farmers in adoption of improved animal husbandry practices and their suggestions/responses to resolve them. Investigation was carried out through personal interviews and questionnaires in the randomly selected 5 villages of Matar Taluka of Kheda district of Middle Gujarat involving 50 respondent dairy farmers. Most of the respondents had medium to high level of knowledge regarding improved animal husbandry practices, i.e. water management practices, reproductive practices, breed improvement, nutritional management, scientific milking and disease control practices. Majority of dairy farmers had economic problem and problems related to management practices, feeding practices. Few of the respondents faced problems regarding marketing. Most of the dairy farmers made suggestions regarding facility of preservation of vaccine and semen at milk co operatives and loan/subsidy facilities for construction of animal shed, purchase of dairy animals, and regular trainings.